Investigating the Causality and Pathogenesis of Primary Sclerosing Cholangitis in Colorectal Cancer Through Mendelian Randomization and Bioinformatics - Jie Jiao; Honglei Wang; Danping Sun; Wenbin Yu (Genetics Research)
Conclusion: Our MR study provides evidence that genetic susceptibility to PSC is significantly associated with an increased risk of colorectal cancer in European populations. Analysis of transcriptomic data suggests that NRG1 can be used as a novel biomarker to predict patient prognosis when colorectal cancer and PSC coexist.